Swirl flow in combustion chambers - Mohammed, Akmal Nizam (2008)
Swirling fluid motion in enclosed chambers was studied using two methods, simulations using computational fluid dynamics, and experimentation using particle image velocimetry. Using the tangential inlet configuration as the basic design, several different swirl generator models were created using computer aided design software. The aim was to see whether a modified design from the original configuration could provide a reduction in the backflow effect that is constantly present in swirling flows. Simulations show that swirl generator inlets that are angled to 45 degrees from the original tangential position results in the backflow being slightly reduced. However, simulations in which the inlet angle was further increased yield inconclusive results. Later in the study, a model prototype of the 45 degrees inlet configuration was created for the purpose of piv experimentation. From the experiments run, it was found that the results were comparable to that of the simulations.